2018
DOI: 10.1016/j.nicl.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Establishing pathological cut-offs for lateral ventricular volume expansion rates

Abstract: BackgroundA percent brain volume change (PBVC) cut-off of −0.4% per year has been proposed to distinguish between pathological and physiological changes in multiple sclerosis (MS). Unfortunately, standardized PBVC measurement is not always feasible on scans acquired outside research studies or academic centers. Percent lateral ventricular volume change (PLVVC) is a strong surrogate measure of PBVC, and may be more feasible for atrophy assessment on real-world scans. However, the PLVVC rate corresponding to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 33 publications
(58 reference statements)
2
29
0
2
Order By: Relevance
“…A minority of patients (5 of 33) in our cohort showed increases in VV in the study period, with no contractions; indeed, this minority was responsible for the significant increase in VV seen at the whole group level. This is in line with conventional expectations that VV of MS patients should steadily increase over time -notwithstanding normal physiological fluctuations (30). The fact that a majority of patients we analyzed showed VV contractions, as well as expansions, beyond the range of variation of healthy subjects suggests that other processes are at work, in addition to neurodegeneration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A minority of patients (5 of 33) in our cohort showed increases in VV in the study period, with no contractions; indeed, this minority was responsible for the significant increase in VV seen at the whole group level. This is in line with conventional expectations that VV of MS patients should steadily increase over time -notwithstanding normal physiological fluctuations (30). The fact that a majority of patients we analyzed showed VV contractions, as well as expansions, beyond the range of variation of healthy subjects suggests that other processes are at work, in addition to neurodegeneration.…”
Section: Discussionsupporting
confidence: 91%
“…However, there was no significant change in BV throughout the study, suggesting that subtle atrophy may be proceeding on a central rather than global level (28,29). It is expected that VV will increase over time in the course of normal aging, and it is indisputable that this is accelerated in MS (19,21,30,31). When studying the VV in MS patients individually, we observed an oscillating behavior in the majority of patients, with VV expansions and contractions.…”
Section: Discussionmentioning
confidence: 80%
“…In this additional analysis of the MS‐MRIUS study, patients in the active disease cohort had an annualized median PBVC of −.38% compared to −.25% in the NEAD cohort, which falls in the category of brain volume loss range classified below the pathological cutoff for MS patients (>−.4%) . Similarly, median annualized PLVCC was 1.76% in the active disease cohort compared to .28% in the NEAD cohort, which is also lower than the recently proposed pathological cutoff for PLVVC (>3.5%) in MS patients, and further validates use of PLVVC in the clinical routine. While these findings have to be interpreted with caution, it was previously reported that accelerated PLVVC is observed in patients with active disease, when compared to PBVC …”
Section: Discussionmentioning
confidence: 63%
“…This finding suggests that for brain atrophy measurement in observational clinical routine studies, assessment of brain atrophy is more feasible by estimating PLVVC on T2‐FLAIR, compared to PBVC or PLVVC using 2D‐ or 3D‐T1‐WI . The MS‐MRIUS study also showed that PLVVC can be realistically incorporated into routine clinical practice, as it correlates with PBVC, its longitudinal assessment is less compromised by changes in MRI hardware, software, or protocol than is the case for PBVC, and its longitudinal assessment has been shown to be possible in over 95% of patients . As previously shown, the MS‐MRIUS study confirmed that annualized PBVC and PLVVC rates in fingolimod treated patients are similar to those reported in the pivotal RCTs .…”
Section: Discussionmentioning
confidence: 93%
“…Following exclusion of five subjects with an interscan interval of less than 12 months, the mean annualised PLVVC was 0.56% (SD 6.30). Approximately 75% (18/24) of these patients had an estimated annualised PLVVC below the threshold value of 3.5% proposed by Dwyer et al 24 to differentiate between pathological and physiological ventricular enlargement. The MSQoL-54 physical and mental health scores improved significantly at each time point following AHSCT within the RRMS cohort, and up to 12 months for physical domains and at 36 months for mental health domains in the SPMS cohort (online supplementary figure 1A,B).…”
Section: Resultsmentioning
confidence: 86%